The American Constitution and religion - Regan, Richard J. (Catholic University of America Press, 2013)
"Regan reconsiders some of the most important Supreme Court cases regarding the establishment clause and the free exercise of religion. Governmental aid to church-affiliated elementary schools and colleges; state-sponsored prayer and Bible reading; curriculum that includes creationism; tax exemption of church property; publicly sponsored Christmas displays--these and other notable cases are discussed in Regan's chapters on the religious establishment clause. On the topic of the free-exercise clause, Regan considers such subjects as the value of religious freedom, as well as the place of religious beliefs in public schooling and government affairs. Important cases concerning conscientious objection to war, regulation of religious organizations and personnel, and western traditions of conscience are also examined."--Publisher description.